If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -19 = 3x + 7 Reorder the terms: -19 + 4x = 3x + 7 Reorder the terms: -19 + 4x = 7 + 3x Solving -19 + 4x = 7 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -19 + 4x + -3x = 7 + 3x + -3x Combine like terms: 4x + -3x = 1x -19 + 1x = 7 + 3x + -3x Combine like terms: 3x + -3x = 0 -19 + 1x = 7 + 0 -19 + 1x = 7 Add '19' to each side of the equation. -19 + 19 + 1x = 7 + 19 Combine like terms: -19 + 19 = 0 0 + 1x = 7 + 19 1x = 7 + 19 Combine like terms: 7 + 19 = 26 1x = 26 Divide each side by '1'. x = 26 Simplifying x = 26
| A(x)=(x-2)(-3x-9) | | x(x+5)=4-15 | | 4(x-2)-16=6(x-2) | | 2x+4=x+32 | | 5(2x+6)x=4 | | (-3x+4xy)-(2x-4xy)= | | 3wx-4v=4x | | 12x+9=52 | | 3h-2(1+4h)+7= | | a+(-2)=5 | | y+(-9)=-14 | | c-(-5)=1 | | v+1=5 | | a-(-3)=1 | | R=7x+4y | | 3(3x+5)x=5 | | 2(x-1)-1=1/2x-6 | | 7/12x10/7 | | 4+5z-6z^2=0 | | 14c-23=65 | | -x-2y=-x | | 8+x=(24-x)-(19-3x) | | 7=d-d+5 | | 7 = d2+ 5 | | 5x+1=6x+1 | | -6k-2=34 | | 9x-4x=5x-2 | | X/30=2 | | K/K^0.25 | | 3j-18=33 | | 5x-12=-52 | | 6=-3-x |